Pawel Starosta-Imre Kovách-Krzysztof Gorlach (eds.): Rural Societies under Communism and Beyond. Hungarian and Polish Perspectives (Lódz: Lódz University Press, 1999) - Duró, Annamária (Szociológiai Szemle, 2024)
-